Current management of atrial fibrillation: an observational study in NHS primary care. Issue 11 (22nd November 2013) - Kassianos, George; Arden, Chris; Hogan, Simon; Dew, Robert; Fuat, Ahmet
Abstract : Objective: To describe National Health Service (NHS) resource use and pharmacological management of atrial fibrillation (AF) in routine UK primary care. Design: Multicentre retrospective study. Setting: Seven primary care practices in England, one in Wales. Patients: Patients with AF were identified and approached for consent. Data were collected on the first 12 weeks post-diagnosis ('initiation') and, for established patients, up to the most recent 3 years of management ('maintenance'). Results: Data collected on 825 patients with AF, 56% men. Mean age (at diagnosis) 70.5 years. Mean 2.4 (SD 2.2) visits to primary care per patient during the initiation phase; 1.5 (SD 1.8) per patient-year during the maintenance phase. Mean 0.4 (SD 0.6) inpatient admissions for AF per patient during the initiation phase and 0.1 (SD 0.3) per patient-year during the maintenance phase. The mean length of hospital stay per admitted patient was 5.6 days during initiation and 6.4 days per patient-year during maintenance. During the initiation phase, 46.1% (143/310) patients received a β-blocker and 97 (31.3%) received no rate/rhythm control. Only 234 (75.5%) patients received thromboprophylaxis in the 12 weeks postdiagnosis and 674 (87.7%) in the maintenance phase. 440 (57.2%) patients were deemed to be at high risk of stroke at the end of the maintenance phase; 55% (242/440) of these were receiving appropriate anticoagulation therapy. Conclusions: The results suggest that there are opportunities for optimisation of treatment and there is significant NHS resource associated with AF management, the details of which are invaluable for future healthcare planning and policy development in this area.